A Modeling Method for Small Packing Particles in Electromagnetic Simulation - Yi Cheng Zhong; Yu Jian Cheng; Yong Fan (International Journal of Antennas and Propagation)
A modeling method for small packing particles is proposed in this paper, especially for the application of the electromagnetic simulation. This method is able to model random distributed and mutual-contacted packing particles efficiently and accurately. This modeling method is faster than a commonly used software, especially for large number of particles. The accuracy of this modeling method is validated by experiments of packing density and effective permittivity. The established model can be easily imported into commercial electromagnetic simulation software.